(untitled) (Research, Society and Development, 2022)
Suicidal and self-harm behaviors are a challenge for Public Health, specifically for adolescent health, requiring intersectoral interventions. In this sense, school environments are potential spaces for the development of prevention strategies for the aforementioned behaviors. The objective of this study was to analyze in the literature effective suicide and self-injury prevention strategies aimed at adolescents in school environments. This is an integrative literature review, carried out from September to October 2021, using the following online databases: Medical Literature Analysis and Retrievel System Online (MEDLINE), Latin American and Caribbean Literature in Science of Health (LILACS), Bibliographic Index Español en Ciências de La Salud (IBECS), Database on Nursing (BDENF), SUS Collection and Psychology Index- Periodicals searched via the Virtual Health Library (BVS) portal and the Education Resources database Information Center (ERIC). When carrying out the steps foreseen in the review, a total of 11 articles resulted that met the eligibility criteria of the study. The suicide and self-harm prevention interventions found in this literature review addressed mental health issues through the strengthening of socio-emotional skills and the programs indicated a predominance of training to recognize the signs of suicidal behavior and referral to mental health professionals, especially the Gatekeeper (guardians of life). Regarding the effectiveness of the included studies, it was verified that there were promising results in most of them, however some of them showed a gaps.